Association of P-glycoprotein expression and response to anthracycline-based neoadjuvant chemotherapy in locally advanced breast cancer (Medical Journal of Indonesia, 2022)
BACKGROUND Neoadjuvant chemotherapy (NACT) has been shown to improve the overall survival of locally advanced breast cancer (LABC) patients with pathological complete response. However, the efficacy may be reduced due to chemoresistance mediated by P-glycoprotein (Pgp). This study aimed to explore the association between Pgp expression and patients’ response to NACT. METHODS A prospective cohort study was carried out from May 2018 to October 2019 at Cipto Mangunkusumo Hospital and Koja Hospital. Treatment-naïve LABC patients were consecutively enrolled in the study. Immunohistochemistry analysis of the biopsy samples was done to semi-quantitatively measure Pgp expression. The clinical response was evaluated after 3 cycles of NACT, while the pathological response was evaluated for subjects who underwent surgery post-NACT. RESULTS Mean age of the subjects was 46.2 (9.6) years old, and most of the cases were invasive ductal (78%) and luminal B subtype (61%). Pgp was strongly expressed in 21/27 subjects (78%). There were no differences between Pgp-positive and -negative subjects for clinical response (relative risk [RR] 1.1, 95% confidence interval [CI] 0.33–4.01, p = 0.61) and pathological response (RR 1.3, 95% CI 0.8–1.9, p = 0.22). Other clinicopathologic variables were not associated with either clinical or pathological responses. CONCLUSIONS These results showed that Pgp is expressed in most LABC patients, but its role as a predictive factor could not be established. However, due to the limited subjects and a lack of standardized Pgp measurement, careful consideration must be done when interpreting these results.